ANALYSIS OF THE MATHEMATICAL REASONING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS IN THE SET MATERIAL - Irawan, Hendra; Cerio Rahmat Fajar; Indah Widiati (LPPM Institut Ahmad Dahlan Probolinggo, 2025)
Mathematical reasoning skills are an important aspect of mathematics learning that needs to be developed from an early age. This study aims to analyze the mathematical reasoning ability of grade VII junior high school students in set materials with a qualitative descriptive approach. The research subjects were selected purposively based on varying levels of mathematical ability (high, medium, and low). Data was collected through mathematical reasoning tests and semi-structured interviews to dig into students' thought processes. The test instruments are arranged based on mathematical reasoning indicators. The results showed that 43.75% of students were in the good category, 43.75% in the fair category, and 12.5% in the low category. These findings indicate that most students have been able to display adequate mathematical reasoning, although there are still weaknesses in drawing conclusions and making mathematical guesses. The implications of this study emphasize the importance of designing adaptive and contextual learning strategies, as well as the need for the integration of cognitive and affective approaches to improve the quality of students' reasoning in mathematics learning.